Sodium Danshensu Inhibits Oral Cancer Cell Migration and Invasion by Modulating p38 Signaling Pathway - Kumar, V. Bharath; Lin, Shu-Hui; Mahalakshmi, B.; Lo, Yu-Sheng; Lin, Chia-Chieh; Chuang, Yi-Ching; Hsieh, Ming-Ju; Chen, Mu-Kuan (Frontiers in Endocrinology, 2020)
Background: Oral squamous cell carcinoma (OSCC) that comprises about 90% of all oral cancer cases is associated with poor prognosis due to its highly metastatic nature. The majority of OSCC treatment options are related detrimental side-effects. Hypothesis/Purpose: The present study aimed at deciphering the effects of a bioactive phytochemical, sodium danshensu, on human oral cancer cell metastasis. Methods and Results: The treatment of FaDu and Ca9-22 cells with different doses of sodium danshensu (25, 50 and 100 μM) caused a significant reduction in cellular motility, migration, and invasion, as compared to the untreated cells. This effect was associated with a reduced expression of MMP-2, vimentin and N-cadherin, together with an enhanced expression of E-cadherin and ZO-1. Further investigation on the molecular mechanism revealed that treatment with sodium danshensu caused significant reduction in p38 phosphorylation; however, phosphorylation of ERK1/2 significantly decreased only in FaDu cells, whereas p-JNK1/2 did not show any alteration. A combination of p38 and JNK1/2 inhibitors with sodium danshensu also reduced the migration in the FaDu and Ca9-22 cell lines. Conclusion: Collectively, the present study findings reveal that sodium danshensu execute anti-metastatic effect by suppressing p38 phosphorylation in human oral cancer. The study identifies sodium danshensu as a potential natural anticancer agent that can be used therapeutically to manage highly metastatic OSCC.